Advanced inter-cell interference management technologies in 5G wireless Heterogeneous Networks (HetNets) - Raisa, Farah; Reza, Asif; Abdullah, Khaizuran (IEEE, 2017)
The future generations of mobile wireless systems such as the 5G technology are expected to be available due to huge demand on network capacity, better end-to-end performance, high mobility and high data rates. Inter-cell interference (ICI) management is one of the paramount issues that should be concerned in multi-tier Heterogeneous Networks (HetNets). Frequency reuse, successive interference cancellation techniques and coordinated multipoint transmissions (CoMP) are some of the popular interference cancellation schemes for mobile wireless networks. However, implementing these methods to the 5G standards with huge network size and capacity is a major challenge in the upcoming decades. In this paper, an extensive qualitative survey on different schemes of interference reduction is provided along with their performance, effectiveness and deficiencies. Key challenges and some guidelines to rework and overcome the shortcomings of the existing schemes are also discussed.